2011
DOI: 10.1002/chem.201003438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tertiary Phosphanes, Arsanes, and Stibanes as Bridging Ligands in Dinuclear Group 9 Complexes

Abstract: The unusual bridging and semi-bridging binding mode of tertiary phosphanes, arsanes, and stibanes in dinuclear low-valent Group 9 complexes have been studied by density functional methods and bonding analyses. The influence of various parameters (bridging and terminal ligands, metal atoms) on the structural preferences and bonding of dinuclear complexes of the general composition [A(1)M(1)(μ-CH(2))(2)(μ-EX(3))M(2)A(2)] (M(1), M(2) = Co, Rh, Ir; A(1), A(2) = F, Cl, Br, I, κ(2)-acac; E = P, As, Sb, X = H, F, CH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…54,55 It is notable that while the lighter PR3 and AsR3 analogues may be also prepared, these are obtained by substitution of the initially formed -SbR3 ligands, suggesting the importance of the RhSbRh unit. Further calculations on the -SbR3 complexes may determine whether it would be appropriate to also consider this as containing a SbR3 as a delocalised donor/acceptor system.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 It is notable that while the lighter PR3 and AsR3 analogues may be also prepared, these are obtained by substitution of the initially formed -SbR3 ligands, suggesting the importance of the RhSbRh unit. Further calculations on the -SbR3 complexes may determine whether it would be appropriate to also consider this as containing a SbR3 as a delocalised donor/acceptor system.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably the most important recent contribution to stibine chemistry has come from Werner and co-workers, who prepared the first examples of bridging ER 3 (E = P, As, Sb) ligands with Sb i Pr 3 (akin to bridging CO) and who showed that metathesis with PR 3 or AsR 3 also led to examples of these as bridging ligands, although the latter complexes cannot be obtained directly . Theoretical studies have been used to probe the bonding in the bridging ER 3 ligands . Although little studied, SbY 3 and SbR 3– n Y n (Y = GeR 3 , SnR 3 , NR 2 , OR, SR, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the rarity of such species, little is known about the nature of the bonding in these complexes. Based on the limited examples, the bridging mode seems to feature a significant component of acceptance by the ligand and is best stabilized by late transition metals in low oxidation states and strongly π-accepting or heavier, more Lewis acidic pnictines …”
mentioning
confidence: 99%
“…Based on the limited examples, the bridging mode seems to feature a significant component of acceptance by the ligand and is best stabilized by late transition metals in low oxidation states and strongly π-accepting or heavier, more Lewis acidic pnictines. 6 There has been a surge of recent interest in the "noninnocent" behavior of coordinated heavy pnictines, which in several cases demonstrate redox reactivity or anion exchange at Pn in preference to the transition metal center. 7,8 They are also prone to hyper-coordination, forming intra-or intermolecular secondary acceptor interactions with electronegative donor atoms; this behavior is enhanced by electronegative substituents on the pnictine, which increase the Lewis acidity of the Pn center.…”
mentioning
confidence: 99%